Virome Structure of the Small Aral Sea - Alexyuk, Madina (Microbiol Resour Announc, 2020)
Here, we present a virome analysis of the surface waters of the Small Aral Sea. In this case, shotgun metagenomic sequencing of the RNA and DNA virus community was used.